Stoichiometry and planktonic communities structure in littoral and pelagic zones of two lakes with different trophic types in Belarus - Zh. F. Buseva; Sh. G. Farahani; V. I. Razlutskij; E. A. Sysova; N. N. Maisak; K. V. Myagkova; P. C. Frost; Ж. Ф. Бусева; Ш. Г. Фарахани; В. И. Разлуцкий; Е. A. Сысова; Н. Н. Майсак; et al. (Doklady of the National Academy of Sciences of Belarus, 2023)
Stoichiometric C : N : P ratios were compared between primary producers in littoral and pelagic ecosystems of mesotrophic relatively shallow lake Obsterno and shallow macrophyte covered low trophic lake Nobisto from May to October over the next two years. Elemental seston ratios of lake Obsterno revealed smaller differences between littoral and pelagic zones in comparison with lake Nobisto in 2017. During the studied period, in the both lakes, the seston C : N and C : P ratios were higher than the Redfield ratio (106 : 16 : 1 C : N : P) on most dates and N : P was always more than 16. Pelagic C : P and N : P ratios in lake Obsterno were the highest in May in 2017, July and September in 2018 with significant differences between littoral and pelagic zones. N : P ratios decreased in October but there were no significant differences among habitats. In lake Nobisto in 2018, seston C : P and N : P ratios increased from May to July in littoral and pelagic zones but then decreased in September to October. Our research shows differences in stoichiometric ratios in littoral and pelagic zones of these two lakes, which indicates food quality (seston C : N : P ratios) differences for zooplankton species depending on season and location. Изучали стехиометрию сестона (соотношения C : N : P) двух мелководных озер разной трофности – мезотрофного озера Обстерно и дистрофного макрофитного типа озера Нобисто в течение двух последовательных лет. Сравнивали сезонные изменения в стехиометрии продуцентов в литоральной и пелагической зонах. Соотношения элементов в сестоне оз. Обстерно выявили меньшие различия между литоральной и пелагической зонами по сравнению с оз. Нобисто в 2017 г. В течение исследуемого периода в обоих озерах соотношения C : N и C : P в сестоне были выше классического соотношения Редфилда (C106 : N16 : P1), а соотношение N : P всегда превышало 16. Соотношения C : P в пелагиали оз. Обстерно имели самые высокие показатели в мае 2017 г., а N : P в июле и сентябре 2018 г. со значимыми различиями между литоральной и ...